Use of anti-osteoporosis drugs in The Tromsø Study: Is undertreatment a problem? - Ntiamoah, Frank Kwame (UiT Norges arktiske universitet, 2016)
Background: Osteoporosis is a major health issue worldwide. Osteoporosis is characterized by the progressive decreasing in bone mass, microarchitecture decline of bone tissue, bone fragility and strength, which leads to an increase in risk of fracture. About a quarter of Norwegian women over 50 years of age were estimated to have the disease in 2010 and Norway has one of the highest reported incidence of hip fractures in the world with over 9000 hip fractures per year. There are numerous effective anti-osteoporosis drugs (AOD) for the prevention and treatment of osteoporosis and fracture. Despite of this, a number of studies have shown that patients are undertreated with AOD after fractures. The aim of the thesis is to describe the pattern of anti-osteoporosis drug use in a general population among persons with osteoporosis defined by self-report or by bone mineral density measurements, with or without fracture. Material and Method: A cross-sectional study was conducted based on data from the sixth survey of the Tromsø study (Tromsø 6), which took place in 2007-2008. The data included information from questionnaires and physical examinations of the total study population (n=12981) and additionally bone mineral density measurements from a subpopulation (n=3663). Results: The prevalence of anti-osteoporosis drug use among participants reporting osteoporosis in the total population was less than 50%. In the subpopulation the prevalence of anti-osteoporosis drug use among participants that are eligible for treatment with anti-osteoporosis drug was under 20%, and only 20% of these participants were aware that they had osteoporosis. Bisphosphonates was the most frequently used anti-osteoporosis drug type. Prevalence of bisphosphonates use among those in need of treatment within the subpopulation was 11%. Conclusion: This study revealed that the prevalence of anti-osteoporosis drug use among persons eligible for anti-osteoporosis drug treatment is very low, although higher among persons reporting that they had both ...